Wireless Johnson Noise Thermometry for Passive Temperature Sensing - Jasmin Falconer; Geneva Ecola; Zerina Kapetanovic (IEEE Journal of Microwaves, 2025)
Johnson noise thermometers (JNTs) are a promising primary thermometer technology for harsh environments, including nuclear plants, industrial agriculture, and space. However, they are impractical to deploy at large scale in resource-constrained environments since they require a constant power supply. This paper presents the first analysis and demonstration of a wireless Johnson noise thermometer (WJNT). It addresses the deployment concerns of JNTs by separating the sensor, a passive antenna, and conductor from the active reader circuitry used to measure temperature. This makes the sensor easily scalable, completely passive, and detectable by a disconnected mobile reader system. In addition, the sensor's conductor can be distanced from its antenna to allow for the sensing of temperatures not accessible to the reader. This paper theoretically derives the signal-to-noise ratio and sensitivity of a WJNT. A proof-of-concept system was designed and evaluated in lab and outdoors to demonstrate its feasibility and effectiveness for use in different applications. The sensitivity, at room temperature, of the prototyped WJNT was measured to be 0.43 to 1 K for integration times ranging from 100 to 10 s using a 20 MHz bandwidth at 965 MHz.